B76 Saphenous nerve block reduces length of stay after epiphysiodesis of the knee – a triple blind randomized superiority trial. (11th August 2022) - Abusaris, CA; Van Rozen, L; Heeg, M; Ott, A
Abstract : Background and Aims: The aim of this triple blind randomized controlled trial was to compare a bilateral single shot saphenous nerve block to placebo in postoperative pain management after percutan epiphysiodesis of the genual growths plates. Methods: We included 44 patients ASA 1–2, aged 12–18 years; 21 patients received single shot nerve blocks with 10 ml ropivacaine 0.5% per leg; 23 patients received their nerve blocks with 10 ml NaCl 0.9% per leg. General anesthesia and postoperative analgesics were standardized. The main endpoint was length of stay (LOS). We further investigated intra- and postoperative opioid consumption, NRS pain scores, time in the post anesthetic care unit, time to walk (with crutches) and overall patient satisfaction. The Regional Ethics Committee Groningen, The Netherlands gave approval. Results: We observed a median LOS of 41 hours in the intervention group versus 48 hours in the placebo group (p= 0.08), which was not statistically significant but clinically relevant in the sense of discharge management and efficiency. We could show overall low painscores (NRS 0–1.6) with significant difference on the first postoperative night (NRS 1.1 vs 0.5) in favour of the intervention. Conclusions: We could not show statistical significant superiority of the saphenous nerve block. The intervention did support the concept of efficient multimodal pain managment on the ward and didn't show drawbacks like delayed ambulation.